A IRRIGAÇÃO DO FEIJOEIRO (Phaseolus vulgaris, L.) - Godoy, O. Pereira; Abrahão, J. T. M.; Godoy Junior, C.; Godoy, R.; Petta, A. (REVISTA DE AGRICULTURA, 2015)
A IRRIGAÇÃO DO FEIJOEIRO (Phaseolus vulgaris, L.)